Physiological responses, bioactivity and differential analysis of protein abundance of the brown seaweed Sargassum (Phaeophyceae, Fucales) submitted to UV radiation - Osorio, Luz Karime Polo (2019)
The distribution and abundance of macroalgae are determined by the resources they demand (e.g. light, carbon dioxide, mineral nutrients, substrate), the effects of environmental factors (e.g. temperature, salinity, water movement, solar radiation), rates of recruitment, mortality and dispersion, and biological interactions (e.g. competition and herbivory). All these aspects are of particular importance in scenarios of environmental and global climate changes, as they determine the susceptibility and survival of organisms and the dynamic of ecosystems. One of the most debated factors that can affect these responses is the influence of UV radiation. Highly energetic photons in the UV radiation range can be absorbed by nucleic acids, lipids, amino acids, proteins, chlorophylls, and carotenoids of the organisms, causing significant cellular damage through photooxidation and oxidative stress, resulting in several vital metabolic changes such as DNA replication, transcription and translation, growth rate and development, photosynthesis and respiration, and promotion of apoptosis. Based on the aforementioned information, the present study intends to contribute to the knowledge of the effect of UV radiation on macroalgae by using Sargassum spp. as biological model by integrating diverse physiological, cellular defenses, biological activities, and proteomic approaches for understanding the impact and sensitivity of this stressor under laboratory conditions